(untitled) - Tô, Kim Thuý (Cần Thơ, 2010)
The study aimed (1) to investigate the high school English teachers' perceptions toward class observation for professional development and (2) to examine the real class observation practice in high school context to provide the implications for effective class observation practice.
Keywords: English teachers,English language,Giáo viên tiếng Anh,Tiếng Anh; Training of,Study and teaching,Foreign speakers,Sự huấn luyện,Dạy và học,Người học ngoại ngữ